The Impact of Technology Awareness, Motivation and Attitude on Intention to Pay with Cryptocurrency for Tourism Services - Rasuolė Andrulienė; Aida Mačerinskienė; Alfreda Šapkauskienė; Saulius Masteika; Kęstutis Driaunys (Organizations and Markets in Emerging Economies)
This study aims to investigate consumer intention to pay for services in the travel and tourism industry using cryptocurrencies. This research investigates the impact of technology awareness, motivational factors and consumer attitudes on the intention to pay for tourism services using cryptocurrency by analyzing data collected from 794 respondents in the Baltic countries (Lithuania, Latvia and Estonia). The empirical findings support the extended Technology Acceptance Model (TAM) and confirm that technology awareness, motivational factors and attitudes towards cryptocurrencies have a statistically significant impact on the intention to use cryptocurrencies to pay for tourism services. The results also suggest that technology awareness has an indirect effect on intention through the mediators of motivational factors and attitude, with motivation indirectly affecting intention through the mediator of attitude towards cryptocurrencies.